Surface roughness and volumetric contraction of a Y-TZP ceramic sintered by microwave energy and by resistive heating - Nayara Fernanda Barchetta; Larissa Guazzelli Nanni; Jean Soares Miranda; Dolores Ribeiro Ricci Lazar; Valter Assui; Guilherme de Siqueira Ferreira Anzalone Saavedra (Brazilian Dental Science)
Objective: The aim of this study was to evaluate a Y-TZP ceramic sintered by a microwave protocol on volume shrinkage and surface roughness. Material and Methods: Twenty four (N=24) Y-TZP discs were fabricated by milling in CAD/CAM for size standardization. The mean final dimensions of the specimens were 15 mm X 1.6 mm. Samples were divided into 2 groups (n=12): conventional resistive heating sintering protocol (C - Control) and microwave sintering protocol (MO - experimental). For the characterization of the specimens, surface roughness (Ra and Rz parameters) was evaluated with a roughness tester, and volume shrinkage was measured with a hand micrometer. Data were statistically evaluated by Student’s t and Mann-Whitney U tests (?=0.05). Results: The roughness results were: 0.25 ?m ± 0.02 (Ra) and 2.68 ?m ± 0.666 (Rz) for the MO samples; 0.26 ?m ± 0.04 (Ra) and 2.73 ?m ± 0.461 (Rz) for the C group (Ra: p = 0.19; Rz: p = 0.81). The shrinkage results was: MO (21.02% ± 2.70) and C (20.10% ± 0.52) (p = 0.274). Conclusion: The conventional and microwave sintering methods were similar regarding surface roughness and volume shrinkage of Y-TZP dental ceramic.